Aplikasi Rekomendasi Resep Menu Meal Plan Berdasarkan TDEE dan Zat Gizi Makro Pengguna Berbasis Web Dengan Pendekatan MCDA Dan EgoSimilar+ - Ivana Jovita Handoko; Henry Novianus Palit; Liliana Liliana (Jurnal Infra, 2022)
Public awareness in Indonesia of the importance of a healthy lifestyle is getting higher today. Having a healthy and ideal body is the dream of people in Indonesia. One way to achieve a healthy and ideal body is to control the intake of calories, carbohydrates, protein and fat in the food consumed (TDEE and macronutrients). Everyone has different needs for TDEE and macronutrients. It is difficult to meet macro needs in accordance with the daily calorie TDEE if you do not understand how to arrange a daily food menu. TDEE and macronutrients should not be lacking nor should they be in excess, while the composition of each macro has a different calorific value for each gram unit in each food ingredient.The meal plan menu recommendation system uses EgoSimilar+ and AHPSort which is the MCDA approach, the method used in this study is used to build the "Dahar" application which is the meal plan recommendation application in this study.The results of the application and the methods used in this application are able to provide recommendations for meal plans with a tolerance of 10% calorie difference. From a scale of 1 to a scale of 5 with the meaning of a scale of 5 being the highest value, a user survey was conducted on the application and recommendation system. From the survey results, the average user satisfaction is 4.45 out of 104 respondents with the dominating scale values being scale 4 and scale 5.